LEGALITAS PENGGUNAAN DRONE YANG MELINTASI BATAS NEGARA BERDASARKAN HUKUM INTERNASIONAL - Neza Zakaria; Sasmini Mintorodihardjo (Faculty of Law Universitas Sebelas Maret, 2015)
This researchis aims to analyze the legality of use of drones crossing international borders under international law and based on the concept of state sovereignty. This research is normative. The sources of this research are secondary resources that collected by study documentation and interviews are analyzed by interpretation and content analysis. The results show there has been no specific regulations related to the operation of the drones. However, based on general international law, the operation of cross-border drone legal if there is a prior agreement, operated in accordance with the principle of general law, and operated by the combatants. A drone without permission does not violate state sovereignty when a state uses his self defense right and the use of the concept humanitarian intervention. Therefore there is a need a law that specifically regulate the operation of drones especially that used to cross the borders of other countries.